Using Instagram Captions to Improve Students’ Vocabulary Mastery - Rosdiani Rosdiani; Sudarkam Ramlan Mertosono; Erniwati Erniwati (Pioneer: Journal of Language and Literature, 2022)
This research aims to determine the effectiveness of using Instagram captions in improving vocabulary mastery of grade eight students of SMPN 4 Tanantovea Donggala, Central Sulawesi. This is a quasi-experimental research design, involving 44 students selected through the total population sampling technique. To collect the data, the paper-and-pencil method with tests (pretest and posttest) was used. Results showed that there was a significant difference between students’ vocabulary mastery before and after the intervention. With p=0.05 and df=42, it was found that the tcounted value of 9.53 is higher than the tcritical value of 1.683. This means the research hypothesis is accepted. In other words, using Instagram captions can improve vocabulary mastery of grade eight students of SMPN 4 Tanantovea Donggala.